Manajemen “Kewirausahaan" Pesantren - Nahrodi, Paiman (Al-aqidah | Jurnal Studi Islam, 2018)
Pesantrens have the independence and ability to manage their economy. The independence and freedom to organize and define the education?s processes include of entrepreneurship. The process of education refers to panca soul or the value of pieties boarding. Pesantren have the sub-culture as a product of indigenous Indonesian culture. Kiai is a prominent actor of the charismatic leaders. Attitudes and principles of pesantren values are customized into become a habit. Pesantren management is full of honesty, discipline, courage and strong commitment to develop the entrepreneurship. Pesantren will educate and train the good entrepreneurship skills of santri. The goal of entrepreneurship?s management is to increase productivity and satisfaction.